Complete mtDNA genomes reveal similar penetrances of maternally inherited type 2 diabetes in two Chinese families. (3rd May 2016) - Yang, Ying; Zhou, Taicheng; Peng, Minsheng; Liu, Yongying; Li, Yiping; Wang, Huawei; Irwin, David M.; Zhang, Yaping
Abstract: Previous work suggests that mitochondrial DNA (mtDNA) derived from the maternal genome has a close affinity with type 2 diabetes. This would support a familial pattern for type 2 diabetes. Thereby, we analyzed complete mtDNA genomes from two families, A and B, from Southwest China that demonstrated maternally inherited type 2 diabetes. Our data support that mtDNA lineages from families A and B belong to haplogroups A4 and D4h1, respectively. This suggests that maternally inherited type 2 diabetes with similar penetrances can arise in Chinese individuals with strikingly different maternal genetic backgrounds. Two private coding region mutations (G13759A in MT-ND5 and G15930A in tRNA-Thr ) were identified in family B. Further evolutionary and phylogenetic analyses suggest that both these mutations have multiple origins and are unlikely to be disease causing.